Penerapan Model Pelatihan Pusdiklat Depdikbud dalam Pelaksanaan Pelatihan Membatik - Hidayat, Wahyu; Nabila, Syahla; Rofi'ah, Fidia Huwaida; Herwina, Wiwin (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2024)
Non-formal education has a very important role in empowering people from various circles with different backgrounds to mobilize society through the educational activities that have been provided to be able to achieve a more prosperous life. These educational activities are carried out through batik training. The research method used is descriptive qualitative. The results of this research are that the training model created by the Education and Training Center of the Ministry of Education and Culture has 5 stages: 1) Needs Analysis, 2) Approach Strategy, 3) Material Preparation, 4) Implementation and 5) Evaluation. This model is applied during batik training, so that training activities can be carried out well and receive a positive response from training participants.